2016
DOI: 10.1186/s40560-016-0182-z
|View full text |Cite
|
Sign up to set email alerts
|

Glycocalyx and its involvement in clinical pathophysiologies

Abstract: Vascular hyperpermeability is a frequent intractable feature involved in a wide range of diseases in the intensive care unit. The glycocalyx (GCX) seemingly plays a key role to control vascular permeability. The GCX has attracted the attention of clinicians working on vascular permeability involving angiopathies, and several clinical approaches to examine the involvement of the GCX have been attempted. The GCX is a major constituent of the endothelial surface layer (ESL), which covers most of the surface of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
97
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(103 citation statements)
references
References 84 publications
3
97
0
3
Order By: Relevance
“…Further studies involving both children and adults with prospective profiling of glycocalyx components are needed to delineate their roles in dengue pathogenesis and potential as prognostic markers. In addition, interventions to attenuate damage or reconstitute the glycocalyx may have therapeutic potential to decrease vascular leakage in dengue32.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies involving both children and adults with prospective profiling of glycocalyx components are needed to delineate their roles in dengue pathogenesis and potential as prognostic markers. In addition, interventions to attenuate damage or reconstitute the glycocalyx may have therapeutic potential to decrease vascular leakage in dengue32.…”
Section: Discussionmentioning
confidence: 99%
“…To be more specific, transmission of shear stress forces to endothelial cells, which are induced by blood flow, causes changes in the structure and architecture of glycocalyx, triggers the release of nitric oxide, and as a result contributes to the regulation of vasomotor tone. Hence, glycocalyx participates, through this rheological mechanism, in the maintenance of homeostasis of the peripheral tissues . Indeed, denudation of the glycocalyx by heparinase III reduced NO production, hence the glycocalyx is deemed to play a significant role in the regulation of vasomotor tone .…”
Section: Discussionmentioning
confidence: 99%
“…30 In agreement with these studies, in our study, we have shown that there is an association between impaired glycocalyx, as assessed by Hence, glycocalyx participates, through this rheological mechanism, in the maintenance of homeostasis of the peripheral tissues. 31,32 Indeed, denudation of the glycocalyx by heparinase III reduced NO production, hence the glycocalyx is deemed to play a significant role in the regulation of vasomotor tone. 33 To this end in our study, we have found a close association between reduced endothelial glycocalyx thickness and impaired coronary flow reserve, which is at least partly NO dependent.…”
Section: Ta B L E 1 Clinical Characteristics Of the Study Populationmentioning
confidence: 99%
“…Endothelial glycocalyx covers the monolayer and plays important role in maintenance of endothelial integrity . Endothelial glycocalyx regulates endothelial barrier, shear stress, and microenvironment of endothelial monolayer as well as its interaction with various blood cells …”
Section: Introductionmentioning
confidence: 99%